2021
DOI: 10.3389/fnut.2021.693412
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic and Improving Function of Lactobacilli in the Prevention and Treatment of Cardiovascular-Related Diseases: A Novel Perspective From Gut Microbiota

Abstract: The occurrence and development of cardiovascular-related diseases are associated with structural and functional changes in gut microbiota (GM). The accumulation of beneficial gut commensals contributes to the improvement of cardiovascular-related diseases. The cardiovascular-related diseases that can be relieved by Lactobacillus supplementation, including hypercholesterolemia, atherosclerosis, myocardial infarction, heart failure, type 2 diabetes mellitus, and obesity, have expanded. As probiotics, lactobacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 220 publications
(236 reference statements)
0
37
0
Order By: Relevance
“…Intestinal Lactobacillus colonies exert protective effect on the heart by regulating atheroinflammatory response, cholesterol metabolism, oxidative stress response, and gut-derived functional metabolites production such as TMAO, SCFAs, LPS, and BA ( Companys et al, 2021 ; Papadopoulos et al, 2022 ). Of note, researchers also support that lactobacillus interventions could significantly impart a cardioprotective role by regulating the abundance and diversity of selective gut microbial flora ( Zhao et al, 2021 ). To exemplify, L. salivarius Ls-33 supplementation changed gut microbiota composition by escalating the Prevotella-Bacteroides–Porphyromonas group/Firmicutes ratio in obese heart patients ( Zhao et al, 2021 ).…”
Section: Genus Lactobacillus and Human Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal Lactobacillus colonies exert protective effect on the heart by regulating atheroinflammatory response, cholesterol metabolism, oxidative stress response, and gut-derived functional metabolites production such as TMAO, SCFAs, LPS, and BA ( Companys et al, 2021 ; Papadopoulos et al, 2022 ). Of note, researchers also support that lactobacillus interventions could significantly impart a cardioprotective role by regulating the abundance and diversity of selective gut microbial flora ( Zhao et al, 2021 ). To exemplify, L. salivarius Ls-33 supplementation changed gut microbiota composition by escalating the Prevotella-Bacteroides–Porphyromonas group/Firmicutes ratio in obese heart patients ( Zhao et al, 2021 ).…”
Section: Genus Lactobacillus and Human Healthmentioning
confidence: 99%
“…Of note, researchers also support that lactobacillus interventions could significantly impart a cardioprotective role by regulating the abundance and diversity of selective gut microbial flora ( Zhao et al, 2021 ). To exemplify, L. salivarius Ls-33 supplementation changed gut microbiota composition by escalating the Prevotella-Bacteroides–Porphyromonas group/Firmicutes ratio in obese heart patients ( Zhao et al, 2021 ).…”
Section: Genus Lactobacillus and Human Healthmentioning
confidence: 99%
“…Limosilactobacillus reuteri is an important resident microflora in the intestines of all vertebrates, including mammals. 34 DS0333 showed a moderate effect on hIO maturation, both on the morphology and marker expression, compared to DS0384, whereas DS0195 and KCTC3594 T showed a weaker effect on hIO maturation ( Figure 1(a–d )), indicating that the intestinal maturation effect of the postbiotic metabolites of L. reuteri is strain-dependent rather than a common characteristic of the respective species. In addition, the active metabolites were detected continually throughout the growth phase and stably concentrated in the culture broth, showing that the intestinal maturation effect of the CFS from DS0384 gradually increased from the exponential to the late stationary phase of growth ( Figure 1(e-h ) and Supplementary Figure S3).…”
Section: Discussionmentioning
confidence: 95%
“…Lactobacillus is generally reported as indicative of healthy microbiota. Related studies indicated that patients with cardiovascular disease or chronic inflammation had fewer proportions of Lactobacillus in the gut 25,26 . Lam et al .…”
Section: Discussionmentioning
confidence: 99%
“…Related studies indicated that patients with cardiovascular disease or chronic inflammation had fewer proportions of Lactobacillus in the gut. 25,26 Lam et al demonstrated that a diet rich in saturated fat could lead to the development of lipogenic liver, which was associated with a significant decrease in the abundance of Lactobacillus. 27 Goldin et al reported that probiotic Lactobacillus was able to increase the production of antiinflammatory metabolites in the host's intestinal epithelial cells, which contributed to the first line of host defenses against enterovirulent bacteria.…”
Section: Discussionmentioning
confidence: 99%